2018
DOI: 10.1177/1934578x1801300719
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds from the Aerial Parts of Malva verticillata and their Anti-diabetic Effect

Abstract: The EtOAc, n-BuOH, and aqueous fractions from the aerial parts of Malva verticillata have been shown to promote significant recovery from alloxan-induced pancreatic islet (PI) damage in zebrafish larvae at 10 μg/mL. Therefore, this study aimed to identify the principal active components of these plant parts and their pharmacological properties. Repeated SiO 2 and octadecyl SiO 2 column chromatography with the aerial parts of M. verticillata led to isolation of four phenolic compounds; these compounds were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…[6] Previous studies have employed fluorescent 2NBDG staining to specifically detect the size of β-cells in zebrafish larvae. [28,29] This study observed a significant decrease in F I G U R E 7 Protective effect of morin on the butylparaben induced β-cell damages in the zebrafish larvae (n = 30/group). The β-cell was stained with 2NBDG stain.…”
Section: Discussionmentioning
confidence: 76%
“…[6] Previous studies have employed fluorescent 2NBDG staining to specifically detect the size of β-cells in zebrafish larvae. [28,29] This study observed a significant decrease in F I G U R E 7 Protective effect of morin on the butylparaben induced β-cell damages in the zebrafish larvae (n = 30/group). The β-cell was stained with 2NBDG stain.…”
Section: Discussionmentioning
confidence: 76%
“…Group VI: cardiotoxicinduced grouptreated group by giving 500 mg/kg/d of M. verticillata (treated group). The extract was administered to the tested animals by oral gavage once a day for 6 weeks and was injected intraperitoneally with a dose of 1 mg/kg of doxorubicin twice a week for 6 weeks [25,26,[29][30][31].…”
Section: Experimental Designmentioning
confidence: 99%
“…found that M. verticillata may become the promising antidiabetic agent. They isolated four phenolic compounds from the aerial part that recovered the size of pancreatic islets (PIs) from zebrafish larvae damaged by treatment with alloxan [14]. Additionally, the outcomes of the Shim et al, [15] study demonstrated that a water extract of M. verticillata seeds inhibited osteoclastogenesis and bone resorption by suppressing the RANKL signaling pathway.…”
Section: Introductionmentioning
confidence: 99%